اختيار تقنية دمج الصور الأنسب لشبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة - القبيلي, مثنى; حاتم, إياد; جبيلي, ثناء (Latakia University Journal -Engineering Sciences Series, 2016)
يعد دمج الصور من أهم الأساليب المتبعة في التعامل مع الصور خاصة في الشبكات محدودة الموارد كشبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة, وهو يصنف إلى تقنيات عاملة في المجال المكاني وأخرى في المجال الترددي. اعتمد هذا البحث على تقنيات الدمج في المجال الترددي للاستفادة من المزايا التي يقدمها, وتم استخدام تحويل التجب المتقطع كونه يلائم خصائص هذا النوع من الشبكات فهو تحويل بسيط وسهل التطبيق ويحتاج لمتطلبات ذاكرة منخفضة. تمت دراسة ثلاثة طرق معتمدة على هذا التحويل وهي DCTav, DCTma, DCTah, وطبقت هذه الطرق على ثلاث مجموعات مختلفة من الصور, وبعد تقييم نتائج المحاكاة من خلال مجموعة من البارامترات تم التوصل إلى أن الطريقة الأنسب لدمج الصور الملتقطة من عقد حساسة داعمة للوسائط المتعددة هي الطريقة DCTma. Image Fusion is one of the most important methods used in image processing, especially in networks with limited resources such as networks of wireless sensors supporting multimedia. It is classified into technologies operating in spatial domain and others in the frequency domain. In this research, Fusion techniques in frequency domain are manipulated to benefit from its advantages. Discrete Cosine Tansform is used because it fits the characteristics of this type of networking where it is simple, easy to implement and requires low memory. Three methods based on this transformation, DCTav, DCTma and DCTah, have been investigated and applied to three different sets of images. The evaluation of simulation results, with different parameters, showed that the DCTma was the most appropriate method to integrate the imagery taken from sensory nodes supporting multimedia.